An example of an almost hyperbolic Hermitian manifold - Cornelia-Livia Bejan; Liviu Ornea (International Journal of Mathematics and Mathematical Sciences)
The almost hyperbolic Hermitan manifolds introduced in [1] were classified for the first time in [2]. In this note we construct an example of an almost hyperbolic Hermitan manifold which belongs to a certain class that we study here.